Perspective of critical factors toward successful public-private partnerships for emerging economies - Anisa Berisha; Alba Demneri Kruja; Eglantina Hysa (Administrative Sciences, 2022)
In the last decades, Albania has started the implementation of a new practice which is partnership with the private sector, named public-private partnership (PPP), due to the inabilities of the public sector to fulfill all its public needs. This represents a crucial ratio related to economic development and the struggle for a fair and transparent implementation process. Critical success factors (CSF) are the significant elements in the partnership which, if properly identified, provide success in implementation. For this reason, the purpose of this study is to highlight the factors which increase the chances of a successful implementation of PPPs in Albania and the items which contribute to each factor. The data used for the analysis were gained through 175 surveys conducted with people working in private and public institutions engaged in PPP. Of the main CSFs, the identification of the right project is ranked most critical to the success of PPP followed by financial capacity, trust, openness and fairness between parties, negotiation and defined revenue stream. The study findings further suggest that the accountability mechanism should be enforced in order for the public sector to act in accordance with the public interest. It is concluded that the findings of the study will guide the PPP stakeholders on the CSFs of PPPs in Albania.
Keywords: 350; Albania; critical success factors; factor analysis; public-private partnership; sustainability management